Suicide and Attempted Suicide Within Inpatient Psychiatric Units: A 10-Year Mixed-Methods Analysis of 143 Serious Events Across 50 Facilities - Matthew A. Taylor; Shawn Kepner (PATIENT SAFETY, 2026)
Background Suicides and attempted suicides occurring within inpatient psychiatric units pose distinct patient safety challenges, yet relatively few prior studies were based on U.S. patient populations and many studies aggregated on- and off-site events, limiting insights. Methods This study examined factors associated with suicide-related serious events reported to the Pennsylvania Patient Safety Reporting System (PA-PSRS). We performed a retrospective mixed-methods analysis of events that occurred during a 10-year period (2016–2025) to identify demographic, method, object, location, and temporal patterns specific to on-unit events. Results Of 143 events, 130 (91%) were attempted suicides and 13 (9%) were suicides. Overall, 57% involved female patients, but 85% of completed suicides were by male patients. Neck compression was the most frequent method (57%); suicides involving neck compression were significantly more likely when a ligature point was used (p=0.004). Suicide-related events were more frequently associated with private areas (bedrooms, bathrooms), early postadmission period (majority occurred within the first five days), the months of October–March, and the evening shift. Conclusions On-unit suicide-related events exhibit distinct demographic, method, object, location, and temporal patterns. These findings clarify where and when events are concentrated and identify areas for further investigation and stakeholder consideration, which may inform refinement of strategies to prevent suicide-related events within inpatient psychiatric settings. Plain Language Summary Although suicides and attempted suicides that happen on inpatient psychiatric units present unique challenges to patient safety, most studies in the last 25 years have focused on patient populations outside the United States, which feature different rules, practices, resources, and cultures that may influence their findings. Many of these studies also included incidents that occurred off the unit, such as when patients absconded or shortly after discharge. In contrast, the present study draws attention to suicide-related events in the United States, specifically events reported in Pennsylvania from 2016 to 2025 that only occurred on the inpatient psychiatric unit. This overlooked focus provides fresh insights into the demographics, methods, objects, locations, and temporal patterns involved with on-unit suicide-related events. For example, of the 143 event reports studied, 130 (91%) were attempted suicides and 13 (9%) were suicides, and 57% involved female patients; however, 85% of the completed suicides were by male patients. Neck compression was used in 57% of cases, and suicides by this method frequently involved ligature points. Events typically occurred in private areas, such as bedrooms and bathrooms, and most occurred within the first five days of admission, from October to March, during the evening shift (3 p.m. to 11:59 p.m.). These trends reveal opportunities for further study and strategies to prevent suicide-related events on inpatient psychiatric units.